Prevalence of mutations in inherited retinal diseases: A comparison between the United States and India. Issue 2 (9th December 2019) - Yohe, Sophia; Sivasankar, Malaichamy; Ghosh, Anuprita; Ghosh, Arkasubhra; Holle, Jennifer; Murugan, Sakthivel; Gupta, Ravi; Schimmenti, Lisa A.; Vedam, Ramprasad; Thyagarajan, Bharat
Abstract: Background: Studies evaluating next‐generation sequencing (NGS) for retinal disorders may not reflect clinical practice. We report results of retrospective analysis of patients referred for clinical testing at two institutions (US and India). Methods: This retrospective study of 131 patients who underwent clinically validated targeted NGS or exome sequencing for a wide variety of clinical phenotypes categorized results into a definitive, indeterminate, or negative molecular diagnosis. Results: A definitive molecular diagnosis (52%) was more common in the India cohort (62% vs. 39%, p = .009), while an indeterminate molecular diagnosis occurred only in the US cohort (12%). In the US cohort, a lower diagnostic rate in Hispanic, non‐Caucasians (23%) was seen compared to Caucasians (57%). The India cohort had a high rate of homozygous variants (61%) and different frequency of genes involved compared to the US cohort. Conclusion: Despite inherent limitations in clinical testing, the diagnostic rate across the two cohorts (52%) was similar to the 50%–65% diagnostic rate in the literature. However, the diagnostic rate was lower in the US cohort and appears partly explained by racial background. The high rate of consanguinity in the Indian population is reflected in the high rate of homozygosity for pathogenic mutations and may have implications for population level screening and genetic counseling. Clinical laboratories may note diagnostic rates that differ from the literature, due to factors such as heterogeneity in racial background or consanguinity rates in the populations being tested. This information may be useful for post‐test counseling. Abstract : Hispanic/non‐White patients had a lower diagnostic rate for retinal disorders on NGS testing and the Indian cohort had a higher rate of homozygous variants. Heterogeneity in racial background may lead to different diagnostic rates within individual populations, which may be important for patient counseling.